DC chopper in the first and third quadrant operation using single-phase matrix converter topology / Mustafar Kamal Hamzah, Ahmad Farid Abidin and Syahrul Afzal Che Abdullah - Hamzah, Mustafar Kamal; Abidin, Ahmad Farid; Che Abdullah, Syahrul Afzal (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2006)
This report presents the successful implementation of single-phase matrix converter (SPMC) as a DC Chopper, which is a variable de voltage from a fix de voltage. Simulation models were developed using MATLAB/Simulink and PSpice to study the behavior of the proposed Pulse Width Modulation (PWM) technique. The results of simulation were then compared with those obtained from an experimental test-rig that was constructed in the laboratory. Due to its pioneering work a resistive load without the introduction of inductance was used to reduce the complexities of the circuit. This could later be extended in the future incorporating other types of load to study the behavior of the SPMC as a DC Chopper.